Optimization of re-irradiation using deformable registration: a case study - Jumeau, Raphaël (BJR Case Rep, 2016)
Re-irradiation is frequently performed in radiotherapy (RT) departments. We present an optimization methodology that takes the previous irradiation into account. A 68-year-old female patient suffering from rectal adenocarcinoma, who had previously undergone RT for metastases to the right iliac bone, presented with a recurrence of metastasis to the L5 and the left sacroiliac joint. Re-irradiation was performed using volumetric modulated arc therapy (VMAT). We proceeded to a registration of the previous RT planning CT and RT doses to the new planning CT. Virtual volumes corresponding to the intersection of the small bowel (SB) and each isodose structure were created. We calculated the maximal dose (D(max)) that each virtual structure could receive and considered them as constraints. We called this technique modified VMAT. We compared this technique with a standard VMAT plan and a three-dimensional RT plan. Using the modified VMAT technique, a total dose of 20 Gy in five fractions of 4 Gy was delivered to the planning target volume without any acute toxicity. A composite dosimetry was realized with each technique to compare the dose given to the already irradiated SB. We calculated the D(max) received by the already irradiated SB in equivalent dose of 2 Gy fractions. The Dmax was 46.8, 60 and 52 Gy for modified VMAT, standard VMAT and three-dimensional RT, respectively. Dose deformation was used to create new constraint structures to optimize the dose delivered to surrounding tissues. This methodology is readily feasible in clinical routine to optimize the re-irradiation process.